Нейтроннi дослiдження структури неполярних магнiтних рiдинних систем з надлишком поверхнево-активних речовин - Bulavin, L. A.; Nagornyi, A. V.; Petrenko, V. I.; Avdeev, M. V.; Alm´asy, L.; Rosta, L.; Aksenov, V. L. (Publishing house "Academperiodika", 2018)
Non-polar magnetic ﬂuid systems with an excess of surfactants have been studied with the use of the small-angle neutron scattering technique. Two types of highly stable ferroﬂuids, magnetite/oleic acid/decalin and magnetite/myristic acid/decalin, with a low (of about 1 vol.%) magnetite content and various acid fractions (up to 25 vol.%) are examined. The aggregation of magnetic particles and surfactant molecules is shown not to occur in the indicated concentration range of the acid molecule excess. The experimental results testify to a change of the interaction between the molecules of oleic and myristic acids in the free (non-adsorbed) state, when they are dissolved in magnetic ﬂuids, and in their solutions in decalin without magnetic particles.